Faktor Dukungan Sosial terhadap Pencegahan HIV pada Ibu Hamil - Ida Leida; Wilis Milayanti; Ridwan Amiruddin (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
HIV is one of the priorities of the disease of death in the sufferer. Programs implemented to prevent mother-to-child transmission of HIV are Prevention Mother To Child Transmission (PMTCT.). This study aims to determine the factors of social support with the efforts of pregnant women in the prevention of HIV transmission from mother to child in the working area of the Puskesmas Jumpandang Baru Center in Makassar. The type of this research is observational analytic with a cross-sectional design. The population in this study were all pregnant women who performed ANC in trimester 1,2, and 3 at the Puskesmas Jumpandang Baru Center in Makassar in years 2017 as many as 420. Sample in this research as many as 104 samples taken by using a systematic sampling method. The data analysis performed was univariate and bivariate with the chi-square test. Based on the results of the study it is known that from 104 respondents there are 65 people who have sufficient HIV prevention efforts. Variables related to prevention of mother-to-child transmission of HIV, peer support (p=0,000), husband support (p=0,002), support of health workers (p=0,000), and attitude (p=0,000). While unrelated variables is parity (p=0,462). There is a relationship between attitude, friend support, husband support, and support of health workers with efforts240 of 246 Ida Leida M. Thaha, et al | MKMI | 16(2) | 2020 | 239-246to prevent transmission of HIV from mother to child. Advice to health workers should be more emphasis on providing information about HIV and PMTCTso it can affect the attitude of pregnant women in the prevention of HIV transmission from mother to child.